Building Up Students’ English Speaking Skills through Dual Meaning Picture - Jusmaniar Nonci (Edumaspul: Jurnal Pendidikan, 2023)
The objectives of this study are: (1) to find out whether or not the use of dual-meaning pictures can build up students’ English-speaking skills; (2) to find out whether or not the use of dual-meaning pictures is interesting in studying English speaking. The researcher applied the Quantitative Method. The sample was chosen using random cluster sampling and assigned two experimental and control groups. Each group consisted of 25 students. In conducting the research, the researcher employed three instruments: a speaking test to see students' speaking skills and a questionnaire to see their interests. The result shows a significant difference in the students' speaking skills between the experimental and the control groups. It was proven by the result of descriptive and inferential statistical analysis of the student's scores. It can be concluded that using dual-meaning pictures is practical, can build up students' speaking skills, and is an exciting medium for teaching English Speaking skills.